Recent progress in transdermal sonophoresis. (19th May 2017) - Ita, Kevin
Abstract: Transdermal drug administration has a number of advantages that cannot be leveraged for therapeutic benefits because of the robust barrier provided by the stratum corneum. One of the promising techniques for circumventing the stratum corneum is sonophoresis – the use of ultrasound for facilitating transdermal drug delivery. In this review, the mechanisms underlying sonophoresis and the utilization of the technique for transdermal delivery are discussed. The challenges of this mode of drug administration have also been highlighted and insight from a number of toxicological studies is described.